2005
DOI: 10.1016/j.seizure.2005.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation in 15 children with therapy resistant epilepsy; its impact on cognition, quality of life, behaviour and mood

Abstract: This study has shown a good anti-seizure effect of VNS, an improvement in seizure severity and in QOL and a tendency to improvement over time regarding behaviour, mood and depressive parameters. The improvement in seizure severity, QOL, behaviour, mood and depressive parameters was not related to the anti-seizure effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 26 publications
5
71
2
Order By: Relevance
“…13,18,27,28,31,54 Moreover, numerous studies found that VNS can benefit attention, cognition, behavior, mood, and quality of life independent of reduced seizure burden. 1,22,24,25,35,41 These findings suggest that consideration of VNS earlier in the course of refractory disease is warranted. 42 No randomized studies have demonstrated long-term benefits of VNS therapy on cognitive, social, or behavioral development or quality of life.…”
Section: Seizure Control and Developmentmentioning
confidence: 98%
“…13,18,27,28,31,54 Moreover, numerous studies found that VNS can benefit attention, cognition, behavior, mood, and quality of life independent of reduced seizure burden. 1,22,24,25,35,41 These findings suggest that consideration of VNS earlier in the course of refractory disease is warranted. 42 No randomized studies have demonstrated long-term benefits of VNS therapy on cognitive, social, or behavioral development or quality of life.…”
Section: Seizure Control and Developmentmentioning
confidence: 98%
“…57 Strong associations between improved seizure severity and QOL have been made, as has been seen in the adult population. 34,58 In fact, Յ80% of patients had an improvement in the parental conception of the child's QOL.…”
Section: Vns For Refractory Seizures In the Pediatric Populationmentioning
confidence: 99%
“…Follow-up assessments were performed at three and nine months after VNS initiation (Table 2B). 23 Delta power …”
Section: Monitoringmentioning
confidence: 99%